Richard Wright - Bone, Robert, 1924-2007 (University of Minnesota pamphlets on American writers, 1969)
Richard Wright - American Writers 74 was first published in 1989. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.